Political relation among the state and international sports organizations: The 2014 FIFA World Cup event in Brazil - Canan, F.; Zardo da Silva, A. F.; Starepravo, F. A. (Physical Culture and Sport. Studies and Research, 2018)
Throughout the men`s 2014 FIFA World Cup event in Brazil (WC-2014), there was an ongoing reflexive debate that stated the possibility that FIFA, due to orders imposed on the state of Brazil, slandered the country`s national sovereignty. However, FIFA`s sovereignty concerning regulations and international football championships is relativized when contrasted to that of the state. Having the WC- 2014 as a concrete object, the aim was to investigate how relations among sports and politics occurred. A qualitative research study was used through the analysis of documents and literature. It was verified that the WC-2014 event was fitting with the patterns of transnational relationships, in which sovereign entities (the state and FIFA) renounce a portion of their external sovereignty for mutual gain. The misfortune appears when this gain is associated with leaders (political or sports) and not the people, which can cause an internal sovereignty issue. Relating to the WC- 2014, the counter-orders generated during the exception period were not due to FIFA`s interference in the national sovereignty, but to the illegitimacy / immorality of the rulers who accepted the conditions of the transnational institution.